Accelerated 3D T2 mapping with dictionary‐based matching for prostate imaging. Issue 3 (28th October 2018) - Roccia, Elisa; Vidya Shankar, Rohini; Neji, Radhouene; Cruz, Gastão; Munoz, Camila; Botnar, René; Goh, Vicky; Prieto, Claudia; Dregely, Isabel
Abstract : Purpose: To develop a fast and accurate method for 3D T2 mapping of prostate cancer using undersampled acquisition and dictionary‐based fitting. Methods: 3D high‐resolution T2 ‐weighted images (0.9 × 0.9 × 3 mm 3 ) were obtained with a multishot T2 ‐prepared balanced steady‐state free precession (T2 ‐prep‐bSSFP) acquisition sequence using a 3D variable density undersampled Cartesian trajectory. Each T2 ‐weighted image was reconstructed using total variation regularized sensitivity encoding. A flexible simulation framework based on extended phase graphs generated a dictionary of magnetization signals, which was customized to the proposed sequence. The dictionary was matched to the acquired T2 ‐weighted images to retrieve quantitative T2 values, which were then compared to gold‐standard spin echo acquisition values using monoexponential fitting. The proposed approach was validated in simulations and a T1 /T2 phantom, and feasibility was tested in 8 healthy subjects. Results: The simulation analysis showed that the proposed T2 mapping approach is robust to noise and typically observed T1 variations. T2 values obtained in the phantom with T2 prep‐bSSFP and the acquisition‐specific, dictionary‐based matching were highly correlated with the gold‐standard spin echo method (r = 0.99). Furthermore, no differences were observed with the accelerated acquisition compared to the fully sampled acquisition (r = 0.99). T2 values obtained in prostate peripheral zone, central gland, and muscle in healthy subjects (age, 26 ± 6 years) were 97 ± 14, 76 ± 7, and 36 ± 3 ms, respectively. Conclusion: 3D quantitative T2 mapping of the whole prostate can be achieved in 3 minutes.